Magnetite nanoparticles coated with beta-cyclodextrin functionalized-ionic liquid: synthesis and its preliminary investigation as a new sensing material - Sinniah, S.; Mohamad, S.; Manan, N.S.A. (Elsevier, 2015)
In this study, a novel surface of modified magnetite nanoparticles Fe3O4 was coated with beta-cyclodextrin-funclionalized ionic liquid (Fe3O4-beta-CD-IL) via the co-precipitation method in alkaline salt medium. beta-Cyclodextrin-functionalized-ionic liquid has been effectively coated onto the surface of Fe3O4 magnetite nanoparticles. The instruments used to investigate the architecture are: Fourier Transform Infrared Spectroscopy, X-ray Powder Diffraction, Electron Microscope-Energy Dispersive X-Ray Spectrometry, Transmission Electron Microscope, Field Emission Scanning Electron Microscope, Vibrating Sample Magnetometer and Brunauer-Emmett-Teller isotherm. A Vibration Sample Magnetometer analysis verified that the Fe3O4-beta-CD-IL attained excellent magnetic properties. The analysis of High Resolution Transmission Electron Microscope shows that the Fe3O4-beta-CD-IL produced monodisperse particles with minimal aggregation. Moreover, electrochemical studies have revealed that this new material showed outstanding ability to recognize Bisphenol A with lower electrochemical potential at 0.5 V than other comparative materials, as well as a higher detection current. Thus, this material has promising potential as a new electrode material in sensor applications. (C) 2015 Elsevier B.V. All rights reserved.